The Application of Risk–Needs Programming in a Juvenile Diversion Program - Wylie, Lindsey E. (Criminal justice and behavior, 2019)
As “gatekeepers” into the juvenile justice system, diversion programs are positioned to prevent future delinquency. Although research on the effectiveness of diversion is mixed, the risk-needs-responsivity (RNR) model may explain how diversion programming that matches youth to services based on their risk and needs may reduce reoffending. Most RNR research has included juveniles at the deeper end of the system, fewer studies have examined RNR with early system-involved youth. The current study explored the application of risk and needs matching in a juvenile diversion program by gender and race/ethnicity. Furthermore, we estimated a survival function to estimate risk and needs alignment on time to recidivism. Although there were no gender differences in the application of RNR, some racial/ethnic differences did emerge. Findings provide support for assessing diversion youth with the Youth Level of Service/Case Management Inventory (YLS/CMI) and applying the RNR framework to early system-involved youth assessed as low to moderate risk.